Intensive care of acute ischemic stroke - Hacke, Werner; Schwab, Stefan; DeGeorgia, Michael (Cerebrovascular diseases, 1994)
This survey summarises some aspects of critical-care treatment of acute ischemic stroke. Special emphasis is put on the management of raised intracerebral pressure, the use of thrombolytic therapy, general management procedures, such as blood pressure control and metabolic monitoring, in acute ischemic stroke. The indications for surgical intervention in major space-occupying infarction are discussed.
Gesehen am 02.06.2025